Polymer-Enabled Additive Manufacturing for Personalized Drug Delivery and Diagnostic Platforms: Materials, Architectures, Quality Control and Clinical Translation - Parthiban Pandian; Veeran Sethuraman; Arvind Kumar Shukla; Arulkumar Nagappan (Polymers, 2026)
Polymer-based three-dimensional (3D) printing has evolved from a prototyping approach toward a manufacturing strategy with emerging clinical relevance for individualized dosage forms, local drug depots, microneedle systems, microfluidic cartridges, biosensor housings and integrated theranostic platforms. Its value arises from the simultaneous control of polymer chemistry, device architecture and process history: infill, porosity, shell thickness, crosslink density, swelling, degradation and surface chemistry can be used as design variables rather than incidental manufacturing outcomes. This review critically synthesizes recent progress in polymer-enabled additive manufacturing for drug delivery and diagnostic applications, with emphasis on thermoplastic and biodegradable polymers, hydrogels, photopolymers, elastomers, conductive composites, stimuli-responsive networks and bioinks. Fused deposition modelling, hot-melt extrusion, semi-solid extrusion, vat photopolymerization, two-photon polymerization, selective laser sintering, binder jetting and inkjet/aerosol jet approaches are compared in relation to drug stability, diagnostic compatibility, feature resolution, scalability and regulatory risk. Particular attention is given to geometry-controlled release, multi-drug printlets, microneedles, implants, scaffold-based local therapy, microfluidic diagnostics, electrochemical biosensors and wearable or closed-loop systems. Translation is discussed through quality-by-design, critical material attributes, critical process parameters, process analytical technology, extractables/leachables, sterilization, point-of-care manufacturing, data integrity and clinical evidence requirements. Future advances should connect polymer–process–property relationships with clinically meaningful use cases, verified quality attributes and realistic regulatory pathways.